Application of quality tools in a fruit processing industry - Ruivo, Alessandra; Wermuth, Tiago Pacheco; Veiga, Itiara Gonçalves (Brazilian Journal of Production Engineering, 2022)
Context: The food industries are of great importance in the Brazilian economic scenario. The quality during product processing is related to the lowest generation of defects and waste. Objective: apply the PDCA methodology in line with quality tools in a fruit processing industry to improve the quality of the production process. Method: the case study pursued to evaluate the production process through the collection of yield data in the pulping batch of Fuji and Pink Lady apples and to analyze variability using quality tools, such as average and amplitude control charts. In addition, a cost analysis was performed based on the yield results observed using the control charts. Results: Through the application of the PDCA cycle, a decision-making structure was created for evaluation in terms of reducing the process costs. It was possible to identify the lack of training of operators and the absence of work instructions, creating an opportunity for elaboration with the responsible engineer. In addition, from the analysis of variability, to propose improvements in the methodology of data collection for validation and application in other fruits processed by the industry. Conclusion: The PDCA Cycle proved to be a great methodology to work in an integrated way with the other quality tools, aiming at improving products and processes and reducing waste during fruit processing, obtaining a forecast of increased production. annual profit of R$ 45,465.57.
Keywords: PDCA; apple; control chart